Dealing with angry customers - Salenger Educational Media (Firm) (Santa Monica, CA : Salenger Educational Media, 1982)
Shows how to deal with angry customers by first dealing with the person's feelings and then by finding a solution to the customer's problem.
Title from data sheet.
Intended audience: College students, adults, and sales personnel.
Keywords: Customer services; Consumer complaints